The Antibiotic Resistance Pattern of Gram-Negative Bacteria in Children Younger Than 24 Months with a Urinary Tract Infection: A Retrospective Single-Center Study over 15 Consecutive Years - Yoon Kyoung Lee; Haejeong Lee; Jong Min Kim; Ji-Man Kang; Sang Taek Lee; Nam Yong Lee; Yae-Jean Kim; Heeyeon Cho (Korean Society of Pediatric Nephrology, 2015)
Purpose: We investigated trends in antibiotic resistance for gram-negative bacteria in infants with a urinary tract infection (UTI) over 15 years at a single institution. Methods: A retrospective chart review was conducted for children younger than 24 months who visited the emergency room and were diagnosed with a UTI between January 2000 and December 2014. We selected urine culture data that grew Escherichia coli and Klebsiella pneumoniae. Baseline clinical information and results of antimicrobial susceptibility tests were analyzed by dividing the 15-year study time frame into three periods (A: 2000-2004, B: 2005-2009, and C: 2010-2014). Results: During the study period, 478 applicable children were identified (E. coli, 89.7% and K. pneumoniae, 10.3%). Antibiotic resistance to third-generation cephalosporins was increased from period A to period C (A, 2.1%; B, 8.3%; C, 8.8%; P=0.025). Resistance to quinolones also showed a steady pattern during periods A to C, although it was not statistically significant (A, 7.9%; B, 9.7%; C, 12.4%; P=0.221). The incidence of Extended-spectrum β-lactamase (ESBL)-producing gram-negative bacteria increased from period A to period C (A, 1.4%; B, 7.6%; C, 8.2%; P=0.012). Conclusion: This study revealed that the common uropathogens E. coli and K. pneumoniae experienced increasing resistance rates against third-generation cephalosporins and a constant antibiotic resistance to quinolones in children younger than 24 months. We also showed a recent increased incidence of ESBL-producing gram-negative bacteria in patients with community-acquired UTIs. Therefore, it is necessary to actively surveil resistance in order to properly select empirical antibiotics.